Screening for Mercury in Aqueous Environmental Samples and Urine Samples Using Thin Layer Chromatography - Agarwal, Rakhi; Behari, Jai Raj (Water environment research, 2007)
A method for screening based on thin layer chromatography (TLC) comprising silica gel 'G' as a stationary phase and benzene as a mobile phase was found to be most suitable for the detection of mercury in aqueous samples and spiked human urine, without digesting the samples. A broad range for the detection of mercury, from 20 μg/L (20 ppb) to 1000 mg/L (1000 ppm), was established, by optimizing the experimental conditions. In urine samples, mercury could be detected also, at levels as low as 50 μg/L (50 ppb) or above. Mercury was detected by complexation with dithizone followed by TLC, also in the presence of other heavy metals, including arsenic, cadmium, lead, copper, iron, zinc, and nickel. The method is simple, cheap, and has no interference of the matrix present in the natural water and aqueous industrial effluent samples obtained from the field. Further, no sophisticated instrument is needed for the detection of mercury.